An unusual and deadly cause for massive haemoptysis. (13th February 2013) - Naha, Kushal; Shetty, Ranjan K; Vivek, G; Magazine, Rahul
Abstract : We report a 47-year-old man with diabetics presenting with massive haemoptysis. Physical examination showed moderate pallor, but was otherwise normal. Evaluation showed normal bleeding and clotting parameters. Aerobic cultures of sputum samples and acid-fast staining were negative. CT showed fusiform aneurysmal dilation of the descending thoracic aorta compressing the left main bronchus with secondary collapse of the left lower and lingular lobes. Massive haemoptysis was attributed to probable erosion of the aneurysm into the left main bronchus. Retrospective questioning failed to elicit pathognomic symptoms of aortic aneurysm including chest pain. While in the hospital, the patient had another bout of massive haemoptysis, requiring endotracheal intubation for airway protection. Chest x-ray revealed homogeneous opacification of the left hemithorax. The patient was treated with antitussives and blood transfusions and referred to a higher centre for endovascular stent grafting of the aneurysm and simultaneous surgical repair of the left main bronchus. Aortic aneurysm is a rare but deadly cause for haemoptysis, as rapid exsanguination can lead to cardiovascular collapse and death.